La fonction de l’imaginaire dans la construction de la problématique en recherche doctorale : obstacle et outil - Constantin Xypas; Renaud Hétier (Recherches en Éducation)
The imaginary factor is re-evaluated in the light of a Bachelardian point of view, as a source of learning but also as a possible obstacle. It is important to understand how this imaginary factor is susceptible to shape our apprehension of the world, of objects and of reality itself. The situation of young doctoral students in social science must take into account the force of their initial intuition and the relation they have with the object of their research which is often another subject. Categorization of imaginary structures as elaborated by Gilbert Durand is a precious tool but one must not stop solely at a description. Research must lead to a synthetic position susceptible to take into consideration the complexity, the contradictions of reality. This contribution describes a procedure that will favour research that accompanies a transition from spontaneous positions to synthetic ones.